Liquidity Risk and Currency Premia - Söderlind, Paul; Somogyi, Fabricius (Management Science, 2024)
The currency market is the world’s largest financial market by trading volume. We show that even in this highly liquid market, exposure to liquidity risk commands an economically significant risk premium of up to 3.6% per year. Liquidity risk is not subsumed by existing currency risk factors and successfully prices the cross section of currency excess returns. Moreover, we find that liquidity risk and carry trade premia are correlated, although this correlation is limited to static rather than dynamic carry trades. Building on this result, we propose a liquidity-based explanation for the carry trade, which adds significant explanatory power to existing theories. This paper was accepted by Lukas Schmid, finance. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2023.01031 .